Critical Thinking Skills Based on Huma Betang Values in Prospective Elementary School and Special School Teachers - Ady Ferdian Noor; Munawir Yusuf; Kokom Komariah (International Journal of Universal Education, 2026)
Critical thinking skill is an essential competence for educators in the era of disruption, yet its development is often detached from socio-cultural contexts. This paper aims to explore the integration of Huma Betang local wisdom values into the development of critical thinking skills for prospective Elementary School and Special Education teachers. Huma Betang, as the life philosophy of the Dayak people in Central Kalimantan, offers fundamental pillars such as Belom Bahadat (ethics), Hapakat (deliberation), Handep (collaboration), and Equality. Through a descriptive-conceptual analysis method, this discussion demonstrates that the internalization of Huma Betang values can transform critical thinking indicators (analysis, evaluation, and inference) into more humanistic and inclusive practices. For prospective elementary teachers, these values strengthen their character in instilling basic reasoning in students. For prospective special education teachers, the value of equality in Huma Betang serves as a critical basis for advocacy and curriculum adaptation for children with special needs. The results of the discussion are that the curriculum includes integrated learning of local wisdom Huma Betang which produces teachers who are not only logically intelligent, but also wise in acting culturally (inclusive, humanistic, and contextual).